2017
DOI: 10.1253/circj.cj-16-1066
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death Phenomenon While Bathing in Japan ― Mortality Data ―

Abstract: Background: Bath-related sudden cardiac arrest frequently occurs in Japan, but the mortality data have not been sufficiently reported. Methods and Results:This prospective cross-sectional observational study was conducted in the Tokyo Metropolis, Saga Prefecture and Yamagata Prefecture between October 2012 and March 2013 (i.e., in winter). We investigated the data for all occurrences in these areas for which the emergency medical system needed to be activated because of an accident or acute illness related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 8 publications
(5 reference statements)
0
35
0
Order By: Relevance
“…It suggests that drowning plays a crucial role in the etiology of bathing-related cardiac arrests. 12 The drowning is an important cause of OHCA.…”
Section: Article P 1144mentioning
confidence: 99%
“…It suggests that drowning plays a crucial role in the etiology of bathing-related cardiac arrests. 12 The drowning is an important cause of OHCA.…”
Section: Article P 1144mentioning
confidence: 99%
“…This phenomenon is unique to Japan and is not seen in other developed countries, including the US, UK, Germany, and France ( 9 ). Few previous studies have reported the actual death toll ( 6 , 11 , 12 ). We recently conducted broad surveillance programs in three areas - Tokyo Metropolis, Saga Prefecture, and Yamagata Prefecture - and revealed the nationwide occurrence of an estimated 19,000 deaths annually ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Few previous studies have reported the actual death toll ( 6 , 11 , 12 ). We recently conducted broad surveillance programs in three areas - Tokyo Metropolis, Saga Prefecture, and Yamagata Prefecture - and revealed the nationwide occurrence of an estimated 19,000 deaths annually ( 11 ). This sudden death phenomenon is rapidly increasing, since the elderly population (≥65 years of age) of Japan is now growing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudden death associated with hot bathing is a frequent occurrence in Japan,1 with estimates of the annual number of deaths of 19 000 2. In 2012, it was reported in the The Daily Telegraph 3 that Japan’s health ministry was to launch an investigation into bath-time deaths because of the large number of fatalities—said to be three times as many as those who died in car accidents.…”
mentioning
confidence: 99%